Effect of heat treatment time on the microstructure and properties of FeCoNiCuTi high-entropy alloy - Qu Huaizhi; Gong Minglong; Zhang Dongdong; Sun Wenda; Liu Fengfang; Bai Jing; Gao Qiuzhi; Zhao Xiang (Journal of Materials Research and Technology, 2023)
In this paper, a FeCoNiCuTi high entropy alloy (HEA) was heat treated at 950 °C for different time durations. After heat treatment for different lengths of time, the FeCoNiCuTi HEA exhibited good thermal stability, and its crystal structure maintained its FCC + Laves phase structure. The magnetic and mechanical properties of the alloy were obviously improved, the saturation magnetization was increased by 33% to 51.7 emu·g−1, and the coercivity had no significant change. After heat treatment for 10 h, the maximum strain was 16.5%, which is approximately 5 times that of the as-cast alloy.